Effect of Mango Puree (Mangifera Indica L) and Pineapple Puree (Ananas Comosus (L.) Merr) Balance on the Characteristics of Fruit Leather Produced - Amila Khairina; Rifa Izmi Wahdaniah; Manika Sunda Peliyanty (Research Collaboration Community (RCC), 2023)
Fruit leather is one type of food that can be used as an alternative to processed food made from fruits. Some of the fruits that can be processed into fruit leather are harum manis mango and pineapple. The purpose of the study is to find out the right balance between mango and pineapple so as to produce fruit leather with good characteristics. The research was carried out at the Chemical Laboratory and Food Processing Laboratory, Faculty of Agriculture, Ma'soem University in the second week of June to the second week of August 2022. The method used in this study is a Randomized Block Design (RAK) method which consisted of 6 treatments and each was repeated 4 times. The treatment is Mango: Pineapple A(0:100), B(20:80), C(40:60), D(60:40), E(80:20), F(100:0). The analysis in this study includes chemical tests and organoleptic tests. Chemical tests consist of analysis of water content and total dissolved solids while organoleptic tests are carried out on the level of preference for color, taste, aroma, and texture. The results showed that the balance of mango and pineapple puree had a significant effect on water content, total dissolved solids, and level of preference for fruit leather texture. Meanwhile, the level of preference for the color, taste and aroma of fruit leather was not significantly different. The organoleptic D(60:40) balance produced the best level of taste and aroma preference.